2018
DOI: 10.1242/bio.033514
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast differentiation of equine induced pluripotent stem cells

Abstract: Bone fractures occur in horses following traumatic and non-traumatic (bone overloading) events. They can be difficult to treat due to the need for the horse to bear weight on all legs during the healing period. Regenerative medicine to improve fracture union and recovery could significantly improve horse welfare. Equine induced pluripotent stem cells (iPSCs) have previously been derived. Here we show that equine iPSCs cultured for 21 days in osteogenic induction media on an OsteoAssay surface upregulate the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 57 publications
(63 reference statements)
1
32
1
2
Order By: Relevance
“…Bone mineralised requires the activity of alkaline phosphatase (ALP) 28 and we demonstrated that over the 21 days of differentiation there is an increase ALP activity. As we reported previously 16 , and similar to human and mouse ESCs 29 , undifferentiated equine iPSCs express a low level of ALP. ALP activity is increased approximately 20.5 fold after 21 days of differentiation in 3D.…”
Section: Saos-2 Cells Seeded Onto the Constructs As Single Cells Exhisupporting
confidence: 81%
See 4 more Smart Citations
“…Bone mineralised requires the activity of alkaline phosphatase (ALP) 28 and we demonstrated that over the 21 days of differentiation there is an increase ALP activity. As we reported previously 16 , and similar to human and mouse ESCs 29 , undifferentiated equine iPSCs express a low level of ALP. ALP activity is increased approximately 20.5 fold after 21 days of differentiation in 3D.…”
Section: Saos-2 Cells Seeded Onto the Constructs As Single Cells Exhisupporting
confidence: 81%
“…We have previously reported the successful 2D differentiation of equine iPSCs into osteoblasts 16 and here we report the use of a novel, thermoplastic 3D printed scaffold to allow in vitro 3D osteoblast differentiation of equine iPSCs.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations